The Comparative analysis of the use of DC motor loads or using inverters and AC motors. - jamaaluddin jamaaluddin; Shazana DA; Darmansyah; Askharina Aulia Tsaalits; Izza Anshory; Mohammad Akmaludin (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2026)
The transition to renewable energy is a global effort to combat climate change and provide sustainable energy. One of the technologies that is developing is the use of solar power plants (SPP), which are capable of providing clean and environmentally friendly energy. This study aims to analyse the performance of the PLTS system in operating two types of electric motors, namely DC (Direct Current) motors and AC (Alternating Current) motors, with the assistance of an inverter. The experiment was conducted using an off-grid PV system with batteries and a solar charge controller (SCC). Measurements were taken of the voltage, current, and power of each system. The results showed that the AC motor produced greater power (86.3 W) after passing through the inverter compared to the DC motor, which only produced 18.4 W. This study provides insights into selecting the appropriate motor type for solar power systems to ensure efficiency and support SDG 7 targets.